Accuracy of methods for detecting an irregular pulse and suspected atrial fibrillation: a systematic review and meta-analysis - Taggar, Jaspal S.; Coleman, Tim; Lewis, Sarah; Heneghan, Carl; Jones, Matthew (Sage, 2015)
Background: Pulse palpation has been recommended as the first step of screening to detect atrial fibrillation. We aimed to determine and compare the accuracy of different methods for detecting pulse irregularities caused by atrial fibrillation.